برصغیر کے فقہی رجحانات کا ارتقائی جائزہ - ڈاکٹر محسنہ منیر (FIKR-O NAZAR فکر ونظر, 2010)
The muslims of Sub-continent gained the knowledge of islam from famous centres of the muslim world in early years of Islam. The trends of this area were under influence of the trends of Hijaz, Iraq, and Syria. Different schools of thoughts of usool-e-fiqh were settled in the muslim world before the fourth century of hijrah. There are different tendencies towards these schools of thoughts in different countries of the muslim world. In the sub - continent there were also more than one trends of fiqh which resulted in the semi conformity and total conformity of different kinds in different times. As the matter of fact, the scholars of the sub - continent did worthy jobs in spreading the light of Islam here.The countless number of muhadisin, qazis and scholars spent their lives in teaching the people of distant areas of the sub-continent.That is why Islam got strong roots in the Indo Pak area. They maintained standards by writing books, fatawas, and established great setup of madaris.